ANALISIS SEKTOR TERTINGGAL KABUPATEN TEBO SEBELUM DAN SESUDAH COVID-19 - Evi Widi Astuti; Miftahul Jannah; Indra Septiawan; Ahmad Syukron Prasaja (Jurnal Ekonomi & Bisnis, 2023)
To improve a country's economic performance, the growth of the Gross Regional Domestic Product (GRDP) from various industries can be utilized. Regional Gross Domestic Product (GRDP) is one of the factors that can be used to determine the level of the economy of a country or a region either on the basis of current prices or constant prices. This Gross Regional Domestic Product (GDP) growth occurs if the area has a leading sector or a base sector with a relatively fast growth rate. This study uses time series data from the Central Statistics Agency (BPS) Jambi Province from 2018 to 2021. The purpose of this research is to identify leading, lagging, developing sectors and potential business fields from the Tebo Regency area between 2018 and 2021. Year 2018 was taken before the Covid-19 Pandemic occurred and in 2021 it was after the Covid-19 incident. This is done using the location quotient analysis method and the dynamic location quotient (DLQ) method.